PENGARUH HARGA KUALITAS PELAYANAN DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMEGANG POLIS DALAM MEMILIH ASURANSI (Studi Kasus Pada Asuransi JiwaSraya Semarang Barat Branch Office) - Rine Mitrasari; Wahyu Hidayat; Reni Shinta Dewi (Universitas Diponegoro, 2013)
This study aimed to determine the effect of price, service quality and brand image of the decision of policyholder in choosing Jiwasraya Insurance. Type of research is explanatory research. With a sample of 95 respondents who use Jiwasraya insurance through non probabiliti sampling technique which is purposive sampling. The analysis technique uses test validity, reliability testing, simple linear regression, multiple linear regression, T test and F test with SPSS tools 16. The results of this study indicate that the price, service quality, and brand image of Jiwasraya Insurance is quite good. Purchasing decisions are also included in good categorization. The influence rate of price on purchase decisions is 35.9%. The influence rate of service quality on purchase decisions is 26.8%. The influence rate of brand image on purchase decisions is 50.5%. Simultaneously, the influence rate of price, service quality and brand image is at 58.5%. Based on data analysis, it can be inferred partially and simultaneously that the price, service quality and brand image significantly influence purchasing decisions and have a strong level of closeness relationship. It is suggested that companies need to enhance the benefits obtained, quality of service and maintain the existence of the company so that the company's existence remains credible and finally leads to higher purchasing decisions.